Impact of Research Methodology on Data Quality and Research Findings - Ojoboh, Toke Marian; Igben, Harvey G.O. (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2024)
The study examined the intrigueing impact of research methodology as the foundation of any research, impacting the accuracy of data collected, the scope of data collected, and the findings. It focused on the interface between research methodology, data quality, and research findings and elucidated on the relationship between research methodology and the reliability, validity, and generalizability of research findings. Focus was also on the identifying the challenges and limitations associated with different research methodologies in ensuring data quality and reliability. Multidisciplinary discipline of systems theory helped to rationalized on how crucial it is to comprehend the dynamic interconnections, feedback loops, and process structure of research. Finding from the study shows that indeed research methodology determines the quality, reliability, validity, and generalizability of research findings while indicating as well that significant differences exist regarding challenges limiting the applicability of findings in different research methods. As a recommendation, faculties and academic programs should ensure they offer numerous research methodology courses that will lay a foundation for students' research.